Hardship Faced by the Displaced Tribal Farm women of Hill District of Assam - Johari, M.; Saharia, K. K.; Borgohain, A.; Ray, M. N.; Khuman, L. S. (Indian Journal of Hill Farming, 2018)
A study on the hardship faced by the displaced tribal farmwomen in hill district of Assam in rearing livestock was carried out by contacting one hundred women farmers each from two districts namely Dima Hasao and Karbi Anglong in Assam. A reliable and valid interview schedule encompassing a check list containing seventeen items was used for data collection. It was found that that the average degree of difficulties faced due to displacement was 18.10 out of the total obtainable score of 51. When they were tested for mean differences, the test revealed no significant level of difference in the districts. Further majority of the respondents revealed that â€œwomen get no time for weaving and craft making â€“ all their time is spent for livestockâ€, â€œthe ladies have to put more labour now for rearing livestockâ€, â€œspare land for the livestock grazing, open grazing fields are not availableâ€, â€œeducation of children has suffered because of their engagement in livestock care and managementâ€, â€œlife of women has become more tedious with no scope for recreation or get together when they have livestockâ€.